Evaluating the Influence of Online Learning on the Professionalism of In-Service Teacher Education at Islamic Higher Education Institutions - Moh Muslih; Muchamad Fauyan; Nur Kholis; Saprolla Rollie C. Deporos (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2024)
The growing importance of online learning in teacher education highlights the need to assess its impact on teacher professionalism. This study examines the effects of online learning within the in-service Teacher Professional Education (TPE) program at a State Islamic Higher Education institution in Indonesia. Using a mixed-methods approach, the research investigates online learning practices, curriculum adaptation, instructor preparation, and professionalism development. The quantitative analysis shows a significant, moderate correlation between online learning and teacher professionalism (R = 0.573), accounting for 32.9% of the variance (RÂ² = 0.329), with a high statistical significance (p < 0.001). Qualitative results support these findings, emphasizing the role of relevant course materials, learning tool development, and instructor feedback in enhancing professionalism. Curriculum adaptation and thorough preparation by lecturers and mentor teachers are also identified as critical to the program's success. While challenges such as limited interaction and internet access persist, online learning has proven to improve teacher professionalism by offering greater accessibility and flexibility. This study concludes that online learning, when implemented with the right strategies, can significantly elevate teacher professionalism. The implications for Islamic education emphasize the potential of online platforms to strengthen teacher development and educational quality.